2014
DOI: 10.3390/rs6042940
|View full text |Cite
|
Sign up to set email alerts
|

Airborne Hyperspectral Images and Ground-Level Optical Sensors As Assessment Tools for Maize Nitrogen Fertilization

Abstract: Estimating crop nitrogen (N) status with sensors can be useful to adjust fertilizer levels to crop requirements, reducing farmers' costs and N losses to the environment. In this study, we evaluated the potential of hyperspectral indices obtained from field data and airborne imagery for developing N fertilizer recommendations in maize (Zea mays L.). Measurements were taken in a randomized field experiment with six N fertilizer rates ranging from zero to 200 kg·N·ha sensors, and airborne data were acquired by fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
73
2
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(84 citation statements)
references
References 44 publications
6
73
2
3
Order By: Relevance
“…Although the attention toward precision farming techniques is increasing, studies providing methods to obtain variable rate N fertilization maps based on remote sensing data are still limited. Among remote sensing techniques it is worth mentioning the recent development of UAVs (Unmanned Aerial Vehicles) in agricultural applications allowing the collection of multispectral and hyperspectral imagery at sub-metric spatial resolution [49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…Although the attention toward precision farming techniques is increasing, studies providing methods to obtain variable rate N fertilization maps based on remote sensing data are still limited. Among remote sensing techniques it is worth mentioning the recent development of UAVs (Unmanned Aerial Vehicles) in agricultural applications allowing the collection of multispectral and hyperspectral imagery at sub-metric spatial resolution [49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the use of chlorophyll meters (CM), which measure leaf chlorophyll content to estimate N nutrition status, has increased among researchers and farmers [10,11]. Hawkings et al [12] found that the adjusted R 2 of the relationship between CM readings and the nitrogen rate difference (ND) for the economic optimum nitrogen rate (EONR) was 0.76 for a maize-maize rotation.…”
Section: Introductionmentioning
confidence: 99%
“…This does not increase grain yield but, instead, wastes fertilizer, increases costs, and can cause nitrate pollution [8]. This problem has led farmers, scientist and politicians to explore how to improve N efficiency, reduce N inputs and prevent water and soil pollution associated with maize production [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Simple regression models usually correlate measured nitrogen content with variables such as chlorophyll, two-band, or three-band spectral indices [16][17][18][19][20][21][22][23]. However, the decoupling of leaf chlorophyll content and LNC might exist in ecosystems where N limitations are not strong [24].…”
Section: Introductionmentioning
confidence: 99%